2011
DOI: 10.4028/www.scientific.net/kem.474-476.2134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanocrystalline and Ti Implantation on the Oxidation Behaviour of Fe<sub>80</sub>Cr<sub>20 </sub>Alloy and Commercial Ferritic Steel

Abstract: Abstract. The oxidation behaviour of developed Fe 80 Cr 20 alloy and commercial ferritic steel at 1173 -1373 K in air is studied. Effects of crystallite size and titanium implantation on the oxidation behaviour of specimens were analyzed based on oxide morphologies and microstructures. Oxide scales characterisations of specimen after oxidized were identified by X-ray diffraction (XRD). The surface morphology of oxide scales were examined with scanning electronic microscope (SEM) and energy dispersive X-ray ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The specific requirements for metallic interconnects include high oxidation resistance and high electrical conductivity of the surface oxide layer (besides, gas tightness, and a specific coefficient of thermal expansion). Sebayang et al [200] have studied the effect of nanocrystalline grain size on various properties of ferritic Fe-20Cr alloy for SOFC application. The oxidation resistances of the nanocrystalline Fe-20Cr alloys (grain sizes 38 and 53 nm) prepared by mechanical alloying and hot pressing were compared with commercially available ferritic Fe-Cr steel, in the temperature range of 1173 K to 1373 K (900°C to 1100°C).…”
Section: B Alumina Forming Nanocrystalline Alloys/coatingsmentioning
confidence: 99%
“…The specific requirements for metallic interconnects include high oxidation resistance and high electrical conductivity of the surface oxide layer (besides, gas tightness, and a specific coefficient of thermal expansion). Sebayang et al [200] have studied the effect of nanocrystalline grain size on various properties of ferritic Fe-20Cr alloy for SOFC application. The oxidation resistances of the nanocrystalline Fe-20Cr alloys (grain sizes 38 and 53 nm) prepared by mechanical alloying and hot pressing were compared with commercially available ferritic Fe-Cr steel, in the temperature range of 1173 K to 1373 K (900°C to 1100°C).…”
Section: B Alumina Forming Nanocrystalline Alloys/coatingsmentioning
confidence: 99%
“…2. SEM Cross-section and EDS line scan profile of the implanted SPS800 oxidized at 900 o C. (Sebayang et al, 2011), it was showed that the improved oxidation resistance was observed as the fine crystallite size of alloy. The improvement in oxidation resistance due to the finer crystallite size of alloy was also in agreement with the study by (Gupta et al, 2010) which could be explained as following.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, growth rate is obserbve when consolidation process [13 -15]. Braking agglomerates or improving homogenous is promoted by using ultrasonic technique [16 -17] and improving high thermal stability of FeCr alloy is achieved when it in nanorange size [9,10], Lanthanum (La) implantated [18,19] and through nickel electroplating [20]. Therefore, increasing properties of raw material is needed.…”
Section: Introductionmentioning
confidence: 99%